Clinical Presentations, Diagnosis, and Management for Pediatric Antral Web—A 20-Year Experience of a Referral Center - Yeh, Pai-Jui; Chao, Hsun-Chin; Chen, Chien-Chang; Lai, Jin-Yao; Lai, Ming-Wei (Frontiers in Pediatrics, 2021)
Background: Antral web is a rare cause of gastric outlet obstruction in children. The presentation is diverse, depending on the degree of obstruction. Unfortunately, the guidance of management is still lacking. Methods: This study retrospectively evaluated the presentations, management, and outcomes of the pediatric antral web based on a 20-year experience in a referral center. Results: A total of 23 cases were included. The median age of diagnosis was 10 months (interquartile range, IQR, 0.8–23 months). Main presentations comprised vomiting (83%) and upper gastrointestinal (UGI) bleeding (48%). Concurrent gastric ulcers were common (68%). A total of 13 cases (57%) underwent interventional treatment. The median duration from diagnosis to intervention (DtI) was 10 days, but five with longer DtI, ranged from 30 to 755 days. Among the 15 cases with concurrent gastric ulcers, 10 patients received intervention, immediately in six but delayed in four. Surgical treatments (N = 12) achieved a cure in 11, with one rescued by endoscopic treatment. Conclusions: Children who suffer from early gastric ulcers with outlet obstruction shall raise the suspicion of the antral web. Complete obstruction madates early intervention. Around half of the cases with adequate feeding and growth need no intervention. Recurrent obstructive symptoms or adjacent ulcers justify a switch from observation to intervention to avoid complications or growth faltering.